2005
DOI: 10.1177/026119290503300308
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia Scoring: The Quantitative Assessment of Hair Loss in Captive Macaques

Abstract: Many captive animals show forms of pelage loss that are absent in wild or free-living con-specifics, which result from grooming or plucking behaviours directed at themselves or at other individuals. For instance, dorsal hair loss in primates such as rhesus macaques ( Macaca mulatta) in research facilities, results from excessive hair-pulling or over-grooming by cage-mates. This behaviour appears to be associated with stress, and is controllable to some extent with environmental enrichment. Quantifying alopecia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…It is possible that for tourist group males, increased stress levels linked to the occurrence of aggressive interactions with tourists (Maréchal et al 2011) may have played a role in their poorer coat condition, since physiological stress inhibits hair growth (Arck et al 2003). Additionally, such aggression may result in stress-related over-grooming, causing increased alopecia (Honess et al 2005). Females may be less affected in this way, due to their less frequent aggressive interactions with tourists (L. Maréchal, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that for tourist group males, increased stress levels linked to the occurrence of aggressive interactions with tourists (Maréchal et al 2011) may have played a role in their poorer coat condition, since physiological stress inhibits hair growth (Arck et al 2003). Additionally, such aggression may result in stress-related over-grooming, causing increased alopecia (Honess et al 2005). Females may be less affected in this way, due to their less frequent aggressive interactions with tourists (L. Maréchal, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Behavior-associated hair loss has been described in many species including nonhuman primates, sheep, dogs, cats, rabbits, guinea pigs, and laboratory rats and mice (Bresnahan et al , 1983; Honess et al , 2005; Reinhardt, 2005). This behavior has been considered abnormal because it is observed almost exclusively in confined animals.…”
Section: Spontaneous Modelsmentioning
confidence: 99%
“…Berg et al (2009) underline that recording the hair coat condition may play an important role in welfare assessment, as early detection of health problems, even when no pathology is expected to occur. On captive primates, different point scales have been suggested for evaluating the quality of fur (Berg et al, 2009;Wolfensohn and Lloyd, 2003) and the presence/absence of hair loss has been used to assess animal welfare in several studies (Honess et al, 2005;Reinhardt et al, 1986;Steinmetz et al, 2006). On farm animals, a study performed by Pritchard et al (2005) in working horses, donkeys and mules found that 8% of the observed animals showed an inadequate hair coat condition, described as matted, dry, and uneven hair.…”
Section: Introductionmentioning
confidence: 99%